The Immunomodulatory Activity of Cinnamomum burmanni Bark Extract on Leucocyte Differentiation of Mice (Mus musculus) In Diabetes Mellitus Model - Martha Kaihena; Abdul Mahid Ukratalo; Amos Killay; Nunun Ainun Putri Sari Banun Kaliky (Postgraduate, University of Mataram, 2024)
Diabetes mellitus frequently coexists with infection, leading to an immunological response characterised by an elevation in leukocyte levels. This research aimed to assess the immunomodulatory activity of an extract derived from the bark of Cinnamomum burmanni on the differentiation of leukocytes in a diabetes mellitus model using mice (Mus musculus). Prior to the administration of therapy, the glucose levels of all mice were assessed. Subsequently, groups K (+), P1, P2, and P3 were administered STZ at 0.2 ml per individual. The blood glucose levels (post-STZ blood glucose) were checked once more on the seventh day. In the event of a rise in blood glucose levels over (>200 mg/dL), subjects belonging to groups P1, P2, and P3 were administered Cinnamomum burmanii extract under the prescribed dosage. The intervention was administered for 14 days, and blood glucose levels were assessed on the final day of experimentation. On the final day of the experiment, blood samples were collected from the mice's tails in order to prepare blood preparations. The findings indicate that the methanol extract derived from cinnamon bark possesses immunomodulatory properties, as evidenced by its ability to decrease the population of eosinophils, lymphocytes, and monocytes while concurrently increasing the amount of neutrophils.